TYPE 1 DIABETES: PREVENTION AND SCREENING IN FOCUS - Miličić, Tanja; Jotic, Aleksandra; Lukic, Ljiljana; Macesic, Marija; Stanarcic, Jelena; Stoiljkovic, Milica; Milovančević, Mina; Rafailovic, Djurdja; Bozovic, Aleksandra; Radisavljevic, Nina; Lalic, Nebojsa (Medical Research, 2024)
It is reported that the prevalence of type 1 diabetes (T1D) is increasing worldwide. Moreover, patients with T1D have a significant reduction in life expectancy, compared to their nondiabetic peers. In that context, prevention of T1D is a burning issue, having in mind multiple unsuccessful attempts in the last 50 years. However, recently there was a turning point in this investigational area when it was shown that it is possible to delay T1D with immunotherapy in people with a high risk for T1D, in stage 2 of prediabetes. Teplizumab, a humanized IgG1 kappa CD3-directed monoclonal antibody modifies disease progression from stage 2 to overt T1D by preserving β-cell function. In the future, T1D prevention studies should include combining immunomodulatory methods through the depletion of diabetogenic cells, strengthening regulatory cells, and islet regeneration, with a focus on the time of start of therapy and the duration of treatment. Primary prevention studies should start earlier, and secondary prevention studies should include more people at risk, which implies screening for T1D in the general population. People with immune markers of risk for T1D can now live without diabetes or with low metabolic risk for many years, which will allow for a reduction in acute and chronic complications of T1D and potentially a final cure. This review presents data from the newest primary, secondary, and tertiary prevention of T1D, as well as novelties in diagnostics, predominantly screening, and therapy of T1D.